2012
DOI: 10.11120/beej.2012.19000003
|View full text |Cite
|
Sign up to set email alerts
|

Technological and Traditional Drawing Approaches Encourage Active Engagement in Histology Classes for Science Undergraduates

Abstract: In order to promote more active engagement of science undergraduates in histology practical classes some technology-based innovations were introduced. First, an interactive pre-lab tutorial was set up using an electronic handset voting system, where guidance on tissue analysis was given. Second, a web-based resource where students could access photomicrographs of tissues, practice formative assessment tasks and review the information from the pre-lab was produced. When the impact of the innovations was evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 24 publications
0
14
0
1
Order By: Relevance
“…This fact also applies to histology teaching in which much effort has been made to boost students' knowledge retention. Both "traditional" and "nontraditional" methods have been used (Hightower et al, 1999), and modalities such as peer teaching (Beck et al, 2016), audiovisual tools (Campos-Sánchez et al, 2014) and technological and traditional drawing approaches (Cogdell et al, 2012;Rafi et al, 2017) have been extensively studied and tested. In addition, virtual microscopy proved to be beneficial in many aspects (Herrmann et al, 2015;Hortsch, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This fact also applies to histology teaching in which much effort has been made to boost students' knowledge retention. Both "traditional" and "nontraditional" methods have been used (Hightower et al, 1999), and modalities such as peer teaching (Beck et al, 2016), audiovisual tools (Campos-Sánchez et al, 2014) and technological and traditional drawing approaches (Cogdell et al, 2012;Rafi et al, 2017) have been extensively studied and tested. In addition, virtual microscopy proved to be beneficial in many aspects (Herrmann et al, 2015;Hortsch, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…All of these strategies can provide welcome variety in the classroom and enhance student learning. Additionally, the use of drawing has been introduced in practical aspects of cell biology, histology, and anatomy courses in order to improve students’ learning (Colton, ; Carney and Levin, ; Nayak and Kodimajalu, ; Cogdell et al, ; Osório et al, ; Greene, ). Empirical evidence that drawing improves learning is consistent with theoretical assumptions that drawings can: (1) lead to the construction of an abstract, heuristic model; (2) enable visual model‐based reasoning (Van Meter et al, ; Quillin and Thomas, ; Pickering, ; Backhouse et al, ); (3) affect students’ cognitive processing; (4) help students guide selective attention and build internal connections (Mayer, ); and (5) improve knowledge retention (Balemans et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Collecting student feedback is an important aspect of a successful implementation of this technology for teaching in a medical school. Various studies have concluded with positive feedback from students regarding the use of VM (Goldberg and Dintzis, 2007;Triola and Holloway, 2011;Cogdell et al, 2012;Tian et al, 2014;Bridge et al, 2015;Leifer, 2015;Van Es et al, 2015). Wayne et al (2013) report that regardless of prior academic ability, students who reported a positive perception of their school's learning environment performed better on a standardized exam than students who reported less positive perceptions.…”
Section: Tip 12 Collect Student Feedback and Surveysmentioning
confidence: 99%